2011
DOI: 10.1111/j.1365-2362.2011.02578.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term intermittent hyperoxic exposures do not enhance erythropoiesis

Abstract: Daily short-term exposures to normobaric hyperoxia do not increase the [EPO] in healthy individuals. The increased O(2) tension suppresses [EPO]. Hence, administration of pure O(2) to enhance erythropoiesis is not warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In accordance with the results obtained in other studies [19,23,26,28] EPO plasma levels as well as kinetics showed a large inter-individual variability.…”
supporting
confidence: 92%
“…In accordance with the results obtained in other studies [19,23,26,28] EPO plasma levels as well as kinetics showed a large inter-individual variability.…”
supporting
confidence: 92%
“…However, clinical trials dealing with this matter are rare [18,19] and other studies have provided contradictory results, possibly due to different criteria and protocols in subjects' selection and treatment [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a clinical study and limited to 48 h has supported the evidence of the NOP effect (Donati et al, 2017). Conversely, Keramidas et al (2011Keramidas et al ( , 2012 suggest that the NOP effect is not always clear cut. However, it is thought that the specific period of hyperoxia and oxygen concentration is key to induce the effect.…”
Section: Introductionmentioning
confidence: 99%